Nonparametric transfer function models with localized temporal effect - Daquis, John Carlo P. (2013)
A semiparametric transfer function model is proposed and estimated using the backfitting algorithm. Simulation studies indicated that the procedure provides robust estimates for the transfer function especially for short time series data. This provides a viable alternative to the parametric transfer function model that requires large number of time points to estimate a number of parameters of the model. Furthermore, in the presence of seasonality or structural change, the procedure generally yields more robust estimates of the transfer function model than the maximum likelihood estimates of the parameters of the model.
Keywords: Nonparametric statistics; Time-series analysis